The impact of electronic waste recycling on industrial product costs (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This research aims to demonstrate the impact of applying electronic waste recycling on industrial product costs, and investing in the field of providing raw raw materials at lower costs, as well as reducing the volume of hazardous electronic waste and its impact on health and the environment. Many conclusions have been reached, the most important of which is that the application of waste recycling electronic technology contributes to reducing industrial product costs and reducing the volume of hazardous electronic waste to preserve the environment. Many recommendations were reached, the most important of which is that the Electronic Industries Company should adopt the process of recycling electronic waste to reduce production costs.